Effects of drying methods and storage time on the aroma and milling quality of rice (Oryza sativa L.) cv. Khao Dawk Mali 105 - Wongpornchai S. (2014)
The effects of drying methods and storage time on the aroma and milling quality of the aromatic rice, Khao Dawk Mali 105, stored as whole grains, were investigated in order to define the most appropriate post-harvest treatment for the rice. Among the six drying methods that were used, namely: modified air at 30 and 40°C, hot air at 40, 50, and 70°C, and sun-drying, the methods that employed lower temperature appeared to provide higher concentrations of the key aroma compound, 2-acetyl-1-pyrroline, and lower amounts of the off-flavour compounds, n-hexanal and 2-pentylfuran, regardless of the storage time. The sun-drying method yielded contrasting results. Overall, during 10 months storage, as the time increased, 2-acetyl-1-pyrroline concentrations decreased whereas n-hexanal and 2-pentylfuran contents increased. Head rice yield was most clearly affected in the sample dried by hot air at 70°C, giving a percentage yield slightly less than half of those obtained by the other drying methods. However, no significant variation in the percentages of whiteness was observed among the rice samples obtained from the different drying methods and storage times. © 2004 Elsevier Ltd. All rights reserved.